Spray Hose Irrigation System Increased Yield of Polyethylene Mulched Shallot - Raka Daniel Lihardo Sumbayak; Anas Dinurrohman Susila (Journal of Tropical Crop Science, 2018)
Spray hose is a micro-irrigation system using perforated hose as for micro irrigation. Shallot conventional cultivation requires lots of water and labor man days therefore is more efficient. Shallot cultivation system needs to be developed to increase yield and to reduce production cost. This research was conducted to compare conventional cultivation methods with using Spray hose and polyethylene mulch for shallot production. This research was conducted in a hydromorphic alluvial soil type at the Center for Tropical Horticulture Studies Field Station in Kersana, Brebes, Central Java (S 6 o, 55’, 20.536”; E 108o, 51”, 50618”) from May to July 2016. The experiment was arranged in a randomized complete block design (RCBD) with a single factor and three levels of planting system, i.e. conventional ‘Surjan’ system without mulch, one line spray hose with mulch, and two lines spray hose with mulch, with five replications. The result showed that shallots production using of polyethylene mulch and two-line spray hose had higher yields than the conventional method. In addition, this system is more efficient in terms of labor requirement. Cost Revenue Analysis shows that conventional cultivation R/C ratio was 1.72, one-line spray hose R/C ratio was 1.92, while two-line spray hose was 2.26. This study demonstrated that the use of polyethylene mulch combined with two-line spray hose significantly improved shallot growth and increased bulb production, and more cost efficient.Keywords: R/C ratio, micro irrigation, labor, ‘Surjan’ system, soil drench, fertilizerConclusionIrrigation of shallot with two-line spray hose resulted in a better crop growth and a higher yield than conventional planting system and one-line spray hose for polyethylene mulched shallot.  Conventional planting system using more water and labor requirement than the two other treatments. Combination of  two-line spray hose and polyethylene mulch had the most eficient cost production of shalot compared to the  conventional system and one-line spray hose.